Stress convulsions in rodents: within a weight-of-evidence framework for human seizure risk - DeGeorge, Joseph J.; Metea, Monica R. (Frontiers in Toxicology, 2025)
In research settings, rodents exhibit a well-documented sensitivity to stress-induced behavioral alterations ranging from stereotypy to convulsions. These events complicate preclinical drug safety assessments where establishing a No-Observed-Effect Level (NOEL) requires distinguishing true pharmacologic seizures from stress-related convulsions, including a type lacking electrographic cortical correlates, referred to as psychogenic nonepileptic seizures (PNES). Stress triggers in preclinical settings include environmental factors and systemic conditioning effects of investigational drugs unrelated to seizure risk. Stress-induced behaviors can bias safety assessments by creating false-positive findings of seizure liability incorrectly attributed to the test compound. This paper highlights situations when stress conditioning is present during rodent seizure liability studies and proposes a Weight-of-Evidence (WoE) approach to differentiate between drug-induced ES and stress-conditioned PNES. It supports applying context-specific criteria for regulatory considerations especially when convulsions are absent in higher species, when there are inconsistent findings across facilities, and when rodents present stereotypy and lack of neuropathological evidence of drug-induced seizures. This approach aims to minimize the misinterpretation of stress-related artifacts as true pharmacologic seizures, providing a framework for more reliable and translatable seizure liability assessments.